Medication Adherence: Truth and Consequences - Brown, Marie T; Bussell, Jennifer; Dutta, Suparna; Davis, Katherine; Strong, Shelby; Mathew, Suja (The American journal of the medical sciences, 2016)
Improving medication adherence may have a greater influence on the health of our population than in the discovery of any new therapy. Patients are nonadherent to their medicine 50% of the time. Although most physicians believe nonadherence is primarily due to lack of access or forgetfulness, nonadherence can often be an intentional choice made by the patient. Patient concealment of their medication-taking behavior is often motivated by emotions on the part of both provider and patient, leading to potentially dire consequences. A review of the literature highlights critical predictors of adherence including trust, communication and empathy, which are not easily measured by current administrative databases. Multifactorial solutions to improve medication adherence include efforts to improve patients' understanding of medication benefits, access and trust in their provider and health system. Improving providers' recognition and understanding of patients' beliefs, fears and values, as well as their own biases is also necessary to achieve increased medication adherence and population health.